The Effects of Unconditional Cash Transfer on The Mental Health of Underprivileged Households in Indonesia - Nun Khalida Auwalun; Prani Sastiono (Syntax Literate, 2022)
Less profitable socioeconomic factors could cause mental health problems like depression and stress symptoms. Previous studies have investigated the effect of cash transfers on physical health, education, and socioeconomic status. However, this study tends to investigate the effects of BLT and BLSM unconditional cash transfers on the mental health of the underprivileged households in Indonesia. In measuring mental health scores, we provide CES-D score with a score range of 0-30, which higher score means better mental health. Using IFLS 2007 and 2014 data and applying the Two-Stage Least Squared method, we found that BLT and BLSM recipients experienced an increase in mental health score by 1.5 points or 6.3% of the CES-D mean score. Our study also suggests that cash transfers affect the mental health of the recipients through two channels: psychological health, i.e., religiosity; and physical health, i.e., the number of disease symptoms. These programs have the potential to increase an individual’s religiosity and reduce the number of disease symptoms, hence, can enforce mental health improvements.